Pemanfaatan Media Youtube Pada Pembelajaran Teks Eksplanasi “Fenomena Alam” Di Kelas VIII SMP - Ai Rosmiati (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
In the 2013 Curriculum, learning Indonesian in schools is text-based or more focused on text. Through these texts, in addition to being taught linguistics, it is also integrated with character education, through reading texts students are able to improve attitudes to have more character. In this study the author will discuss learning Indonesian which takes explanatory text material with the help of YouTube and studies natural phenomena that occur. This research is in the form of observation and student questionnaires. at the end of the conclusion in this article that there was a change in increasing student learning outcomes before and after using YouTube-assisted media on explanatory text learners, the final calculation used the SPPS application and obtained results that experienced changes in the normality test of students before using Youtube-assisted media of 0.751 and after using Youtube-assisted media of 0.503. because the sig value of the two classes is greater than 0.05, it can be concluded that both data have a "Normal" distribution, while the simple t test obtained the results of students before using Youtube-assisted media of 65,640 and after using Youtube-assisted media of 86,200. Descriptively, it can be concluded that there is a difference in the average value of students' ability to write explanatory text before and after using Youtube-assisted media.